EGFR pathway biomarkers in erlotinib-treated patients with advanced pancreatic cancer: translational results from the randomised, crossover phase 3 trial AIO-PK0104 - Böck, Stefan; Jung, A.; Laubender, R. P.; Neumann, J.; Egg, R.; Goritschan, C.; Vehling-Kaiser, U.; Winkelmann, C.; Fischer von Weikersthal, L.; Clemens, M. R.; Gauler, T. C.; Märten, Angela; et al. (British journal of cancer, 2013)
We aimed to identify molecular epidermal growth factor receptor (EGFR) tissue biomarkers in pancreatic cancer (PC) patients treated with the anti-EGFR agent erlotinib within the phase 3 randomised AIO-PK0104 study.
published online 20 November 2012
Gesehen am 27.11.2020